Proceso de atención de enfermería en adulto mayor con miasis ocular. - Vera Casal, Carlos Vicente (2021)
The nursing care process is considered as a logical, rational, systematic and organized method, it allows to administer care in an individualized way, focusing on the identification of its needs. The present clinical case deals with an 86-year-old patient with ocular myiasis, who attends the medical attention center, entering through the emergency area accompanied by a neighbor, presenting pain, redness, edema and a sensation of movement within the orbital cavity, patient He refers not to have noticed any bite, states that he does not comply with adequate hygiene, also there are stray animals near him, upon admission of the patient the doctor assesses it, in the physical evaluation the presence of injury is evidenced at the level of the right orbital cavity, existence larvae, it is required to perform laboratory tests and assessment by the nursing staff. When carrying out the assessment of the nursing care process (ECP) in a patient with ocular myiasis, a clinical analysis was carried out by Marjory Gordon's functional patterns, in addition to a cephalo-caudal and systems assessment, taking into account the general objective of By using the nursing care process (PAE), an alteration of various functional patterns is evidenced, proceeding to elaborate the nursing diagnoses and nursing activities according to the needs of the patient. Follow-up is carried out in which compliance with the nursing interventions is evidenced.